Salivary biomarkers of cellular damage and oxidative stress following of lower third molar surgical removal - Dias, Layani Bertaglia; Tonzar, Thaline Teixeira; Santos, Damaris Raíssa dos; Souza, Rayne Oliveira; Ribas, Tayná Buffulin; Silva, Leonardo de Freitas; Reis, Erik Neiva Ribeiro de Carvalho; Ponzoni, Daniela; Dornelles, Rita Cássia Menegati; Nakamune, Ana Cláudia de Melo Stevanato; Chaves-Neto, Antonio Hernandes (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Background: The aims of this study were the temporal analysis of salivary biomarkers of cellular damage and oxidative stress following of lower third molar surgical removal from healthy patient and without postoperative complications. Material and Methods: Three whole unstimulated saliva samples were collected from each of 17 patients (8 men, 9 women) before surgery, 1 and 7 days after lower third molar surgical removal using the expectoration (or 'spit') method. Salivary flow rate (SFR), pH, buffer capacity (BC) were measured, immediately after collection. The samples were centrifuged and the supernatants were stored in aliquots at -80°C until analysis. Salivary thiobarbituric reacting substances (TBARs), total antioxidant capacity (TAC), haemoglobin (Hb), total protein (TP), uric acid (UA), acid phosphatase (ACP), tartrate-resistant acid phosphatase (TRAP), alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and lactate dehydrogenase (LDH) were measured by spectrophotometric method. Results: There were no significant differences between pre- and post-surgical SFR, pH, BC, or TP. One day after extraction were detected a significant increases in Hb, TBARs, ACP, TRAP, ALP, AST, ALT, and LDH activities, and decreases of UA and TAC levels were observed. Seven days after extraction, only AST (higher) remained increased compared to pre-surgical levels. Conclusions: The surgical removal of impacted lower third molars increases salivary biomarkers of cellular damage and oxidative stress, and decreases the TAC in the early postoperative. Considering these issues, our data open new perspectives of a possible use of these parameters as biomarkers for screening and monitoring of patients vulnerable to the development of postoperative complications. Descriptors: Saliva; Biomarkers; Oral Surgical Procedures; Oxidative Stress; Enzymes; Thiobarbituric Acid Reactive Substances. References Majid OW, Mahmood WK. Effect of submucosal and intramuscular dexamethasone on postoperative sequelae after third molar surgery: comparative study. Br J Oral Maxillofac Surg. 2011;49(8):647-52. Larjava H. Oral wound healing : cell biology and clinical management. Oxford: Wiley-Blackwell; 2012. XVI, 408 p.p Mohn CE, Steimetz T, Surkin PN, Fernandez-Solari J, Elverdin JC, Guglielmotti MB. Effects of saliva on early post-tooth extraction tissue repair in rats. Wound Repair Regen. 2015;23(2):241-50. Ozmeric N, Mollaoglu N, Elgun S, Devrim E. Impact of chlorhexidine mouth rinse use on postextraction infection via nitric oxide pathway. Inflamm Res. 2010;59(6):437-41. Dos Santos DR, Souza RO, Dias LB, Ribas TB, de Oliveira LCF, Sumida DH et al. The effects of storage time and temperature on the stability of salivary phosphatases, transaminases and dehydrogenase. Arch Oral Biol. 2018;85:160-65. Dabra S, China K, Kaushik A. Salivary enzymes as diagnostic markers for detection of gingival/periodontal disease and their correlation with the severity of the disease. J Indian Soc Periodontol. 2012;16(3):358-64. Cesco Rde T, Ito IY, de Albuquerque RF Jr. Levels of aspartate aminotransferase (AST) in saliva of patients with different periodontal conditions. J Clin Periodontol. 2003;30(8):752-55. Cunha-Correia AS, Hernandes Neto A, Pereira AF, Aguiar SM, Nakamune AC. Enteral nutrition feeding alters antioxidant activity in unstimulated whole saliva composition of patients with neurological disorders. Res Dev Disabil. 2014;35(6):1209-15. Nagler RM, Klein I, Zarzhevsky N, Drigues N, Reznick AZ. Characterization of the differentiated antioxidant profile of human saliva. Free Radic Biol Med. 2002;32(3):268-77. Miricescu D, Totan A, Calenic B, Mocanu B, Didilescu A, Mohora M et al. Salivary biomarkers: relationship between oxidative stress and alveolar bone loss in chronic periodontitis. Acta Odontol Scand. 2014;72(1):42-7. Bansal N, Gupta ND, Bey A, Sharma VK, Gupta N, Trivedi H. Impact of nonsurgical periodontal therapy on total antioxidant capacity in chronic periodontitis patients. J Indian Soc Periodontol. 2017;21(4):291-95. Wang Y, Andrukhov O, Rausch-Fan X. Oxidative stress and antioxidant system in periodontitis. Front Physiol. 2017;8:910. Cutando A, Arana C, Gomez-Moreno G, Escames G, Lopez A, Ferrera MJ et al. Local application of melatonin into alveolar sockets of beagle dogs reduces tooth removal-induced oxidative stress. J Periodontol. 2007;78(3):576-83. Bassoukou IH, Nicolau J, dos Santos MT. Saliva flow rate, buffer capacity, and pH of autistic individuals. Clin Oral Investig. 2009;13(1):23-7. Kamodyova N, Banasova L, Jansakova K, Koborova I, Tothova L, Stanko P et al. Blood contamination in saliva: impact on the measurement of salivary oxidative stress markers. Dis Markers. 2015;2015:479251. Hartree EF. Determination of protein: a modification of the Lowry method that gives a linear photometric response. Anal Biochem. 1972;48(2):422-27. Granjeiro JM, Taga EM, Aoyama H. Purification and characterization of a low-molecular-weight bovine kidney acid phosphatase. An Acad Bras Cienc. 1997;69(4):451-60. Henry RJ, Chiamori N, Golub OJ, Berkman S. Revised spectrophotometric methods for the determination of glutamic-oxalacetic transaminase, glutamic-pyruvic transaminase, and lactic acid dehydrogenase. Tech Bull Regist Med Technol 1960;30:149-66. Huijgen HJ, Sanders GT, Koster RW, Vreeken J, Bossuyt PM. The clinical value of lactate dehydrogenase in serum: a quantitative review. Eur J Clin Chem Clin Biochem. 1997;35(8):569-77. Buege JA, Aust SD. Microsomal lipid peroxidation. Methods Enzymol. 1978;52:302-10. Benzie IF, Strain JJ. The ferric reducing ability of plasma (FRAP) as a measure of "antioxidant power": the FRAP assay. Anal Biochem. 1996;239(1):70-6. Trivedi RC, Rebar L, Berta E, Stong L. New enzymatic method for serum uric acid at 500 nm. Clin Chem. 1978;24(11):1908-11. Shaila M, Pai GP, Shetty P. Salivary protein concentration, flow rate, buffer capacity and pH estimation: A comparative study among young and elderly subjects, both normal and with gingivitis and periodontitis. J Indian Soc Periodontol. 2013;17(1):42-6. Hosseini-Yekani A, Nadjarzadeh A, Vossoughi M, Reza JZ, Golkari A. Relationship between physicochemical properties of saliva and dental caries and periodontal status among female teachers living in Central Iran. J Int Soc Prevent Community Dent. 2018;8(1):48-55. Jafari SM, Motamedi MH, Jafari M, Tabeshfar S, Jafari M, Naghizadeh MM. Impacted lower third molars: Can preoperative salivary pH influence postoperative pain? Natl J Maxillofac Surg. 2010;1(2):123-26. Kejriwal S, Bhandary R, Thomas B, Kumari S. Estimation of levels of salivary mucin, amylase and total protein in gingivitis and chronic periodontitis patients. J Clin Diagn Res. 2014;8(10):ZC56-60. Gutierrez-Corrales A, Campano-Cuevas E, Castillo-Dali G, Serrera-Figallo MA, Torres-Lagares D, Gutierrez-Perez JL. Relationship between salivary biomarkers and postoperative swelling after the extraction of impacted lower third molars. Int J Oral Maxillofac Surg. 2017;46(2):243-49. Hannig C, Spitzmuller B, Hannig M. Transaminases in the acquired pellicle. Arch Oral Biol. 2009;54(5):445-48. Hannig C, Spitzmuller B, Miller M, Hellwig E, Hannig M. Intrinsic enzymatic crosslinking and maturation of the in situ pellicle. Arch Oral Biol. 2008;53(5):416-22. Rodriguez PG, Felix FN, Woodley DT, Shim EK. The role of oxygen in wound healing: a review of the literature. Dermatol Surg. 2008;34(9):1159-69.